Stunting Risk Factors In Children Under 5 Years Old In Indonesian Border Regions (North Kalimantan-Malaysia) - Ika Yulianti; Nurasmi Nurasmi; Rahmi Padlilah (International Journal of Health and Pharmaceutical (IJHP), 2022)
Stunting in children becomes a health problem that gets priority and must be addressed immediately, especially at the border. Stunted development, decreased cognitive function and immune function as well as the risk of diabetes mellitus, coronary heart disease, hypertension and obesity are the effects of stunting. The aim of the study was to systematically find out the risk factors for stunting on the North Kalimantan-Malaysia border. Methods of using systematic review. Research from as many as 454 articles later in PRISMA analysis into 10 articles came from databases such as Pubmed, Science Direct, google scoolar. The results showed that the risk factors for stunting are Birth Length, Exclusive breast milk companion food, exclusive breastfeeding, family opinion, maternal factors namely age, attitude, occupation, knowledge, education and height.